Padrões de desfolha em pastagem consorciada de sorgo forrageiro e papuã - Rodrigues, Dinah Pereira Abbott (2022)
Expanding knowledge about defoliation patterns in mixtures is crucial to provide grazing strategies targeting to optimize forage production, as it directly influences plant behavior to animal grazing. The work was carried out aiming to evaluate defoliation intensity and frequency of defoliation in pasture of forage sorghum (Sorghum bicolor (L.) Moench.) and alexandergrass (Urochloa plantaginea (Link) Hitch) grazed by beef heifers, kept under continuous stocking. The experimental design was completely randomized, with measures repeated in time, with two treatments, totalizing nine replications. The treatments evaluated were forage species, forage sorghum and alexandergrass, during pasture phenological stages. For variables from structural characteristics of mixture, five evaluation periods (n = 90) were considered. For variables from defoliation patterns, there were four evaluation periods (n = 72). The variables forage mass, forage supply and stocking rate were evaluated only as a function of experimental periods. The overall leaf blade defoliation intensity (%) was higher for forage sorghum, when compared to alexandergrass, in the second and fourth evaluation periods. The overall leaf blade defoliation frequency (number of defoliation blade-1 day-1) was higher for forage sorghum (0.12), to the detriment of alexandergrass (0.09). The total leaf blade mass (kg DM ha-1) was higher and lower in the first and fifth evaluation periods, respectively. In addition, alexandergrass maintained the amount of leaf blade mass in the last evaluation periods, while forage sorghum was already starting pre-flowering phenological stage. In this context, beef heifers have their defoliation patterns altered depending on phenological stage of mixture. A partial preference for forage sorghum was observed, however alexandergrass proved to be a forage species that ensures longevity for the system. Therefore, the mixture of these species is favorable and recommended.